Exploration of Family Rutaceae in Garden Eden 100 Tobasa Agrowisata Forest - Nurhasnah Manurung; Pandu Prabowo Warsodirejo (Bioscience, 2019)
Research in the Eden 100 agrotourism forest located in the area of Lumban Rang, Sionggang Utara Village, LumbanJulu District, Kab. Toba Samosir North Sumatra has been carried out for 3 months using "Survey or Exploration Method". The aim of this research is to find out data on plant species of family Rutaceae in the Eden Park area 100 and then make herbs and to produce learning devices in the form of dabbing as ingredients teach Biology courses in High Plant Taxonomy. The results showed that there were 9 types of plant family Rutaceae with the Genus Citrus as many as (6), Genus Zanthoxylum (1), Genus Triphasia (1), Genus Aegle (1), so the most dominant is the Genus Citrus. such as Lime (Citrus aurantifolia), Andaliman (Zanthoxylumachanthopodium), Orange Purut (Citrus hystrix DC), Tiger Orange (Citrus medica), Kingtit Orange (Triphasiatrifolia), Lemon Orange (Citrus lemon), Kasturi Orange (Citrus madurensis) , Sweet / Squeezed Oranges (Citrus sinensis), AegleMajamarmelos (L.) Corr. The Rutaceae family plant found in the Eden 100 agrotourism forest is still relatively small when compared with the total total genus Rutaceae 150 genera and 1500 species